2018
DOI: 10.1038/s41598-018-34031-4
|View full text |Cite
|
Sign up to set email alerts
|

Missing elimination via membrane vesicle shedding contributes to the diminished calcium sensitivity of listeriolysin O

Abstract: The lytic capacity of cholesterol-dependent cytolysins is enhanced in the extracellular calcium-free environment through a combination of limited membrane repair and diminished membrane toxin removal. For a typical neurotoxin of the group, pneumolysin, this effect has already been observed at reduced (1 mM) calcium conditions, which are pathophysiologically relevant. Here, we tested another neurotoxin of the group, listeriolysin O from L. monocytogenes, active in the primary vacuole after bacterium phagocytosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In case of SLO, the archetype of a CDC produced by S. pyogenes, pores are repaired by Ca 2+ -dependent and annexin-mediated fusion of the plasma membrane and shed as microvesicles into the extracellular space (ectocytosis) [76][77][78]. The same mechanism of Ca 2+ -dependent microvesicle shedding was reported for the CDC listeriolysin O (LLO), perfringolysin O (PFO), intermedilysin (ILY), and PLY [79][80][81]. Another possibility to prevent cell lysis is the Ca 2+ -dependent endocytic removal and internal degradation of the plasmalemmal lesion, which has also been described for SLO [52], as well as for other pore-forming toxins [82,83].…”
Section: Nptr Cells Reseal Sly-induced Cell Damage More Efficiently Tmentioning
confidence: 70%
“…In case of SLO, the archetype of a CDC produced by S. pyogenes, pores are repaired by Ca 2+ -dependent and annexin-mediated fusion of the plasma membrane and shed as microvesicles into the extracellular space (ectocytosis) [76][77][78]. The same mechanism of Ca 2+ -dependent microvesicle shedding was reported for the CDC listeriolysin O (LLO), perfringolysin O (PFO), intermedilysin (ILY), and PLY [79][80][81]. Another possibility to prevent cell lysis is the Ca 2+ -dependent endocytic removal and internal degradation of the plasmalemmal lesion, which has also been described for SLO [52], as well as for other pore-forming toxins [82,83].…”
Section: Nptr Cells Reseal Sly-induced Cell Damage More Efficiently Tmentioning
confidence: 70%
“…In contrast, reduction or lack of calcium did not increase cell death from LLO to the same extent that it increased PLY-dependent killing [269,270]. While reducing calcium from 2 mM to~1 mM or 0 mM increased PLY killing of glial cells up to 10-fold, it improved LLO-mediated killing only 2.5-fold [269,270]. This was attributed to a decrease in the extent of vesicle shedding triggered by LLO compared to PLY, though shedding was observed for both CDCs [270].…”
Section: Listeriolysin O (Llo)mentioning
confidence: 92%
“…While small pore-forming toxins such as aerolysin did not show calcium dependence [78], CDCs such as SLO, PFO, or PLY generally triggered calcium-dependent repair mechanisms [35,47,55,56,268]. In contrast, reduction or lack of calcium did not increase cell death from LLO to the same extent that it increased PLY-dependent killing [269,270]. While reducing calcium from 2 mM to~1 mM or 0 mM increased PLY killing of glial cells up to 10-fold, it improved LLO-mediated killing only 2.5-fold [269,270].…”
Section: Listeriolysin O (Llo)mentioning
confidence: 95%
See 1 more Smart Citation
“…As observations are usually made at a very early time point after addition of toxin, it is tacitly assumed that cellular channel forming proteins or ruptures do not contribute to the influx of dye. At any rate, important insight into the consequences of membrane damage, e.g., [67,68], and various mechanism of CIDRE [72,73,74,75,76,77,78,79,80], has been gained by studies on CDC. In essence, these studies showed that removal of CDC pores from the plasma membrane is important for recovery of target cells and that this may involve uptake or shedding of membrane lesions.…”
Section: Phlyp As a Paradigm Of Membrane Repairmentioning
confidence: 99%